Industrial process optimization through advanced HMI systems: exploring the integration of IoT and AI - Arce Santillan, Dora Yvonne; Nolasco Sandoval, Luis Alfredo; Martinez Santillán, Albert Isaac; Avalos Yataco, Percy Jesús; Presentación Quispe, Higmmer Santiago; Hercilla Huapaya, Nelson Rene (Institute of Advanced Engineering and Science, 2024)
Facing the challenge of improving efficiency and stability in industrial processes, this study examines the impact of implementing advanced human-machine interface (HMI) systems, complemented by the internet of things (IoT) and artificial intelligence (AI). The integration of a PLC and HMI-controlled system has resulted in a 22.85% increase in efficiency, stabilizing production and reducing process variability. Tools such as PLCSIM and TIA PORTAL were crucial for validating control logic and programming. Additionally, the study explores the potential of AI and IoT to amplify these benefits, suggesting a significant advancement in automation that could transform operational efficiency and quality in related industries. These findings provide a relevant framework for companies looking to integrate emerging technologies into their operations, promoting continuous improvement and more informed management.